Mixed Solvothermal Synthesis of Sb2Se3 Whiskers Assembled by Nanobelts - Hu, Hanmei; Deng, Chonghai; Zhang, Xiaoyu; Yang, Benhong (Asian Journal of Chemistry, 2013)
By adopting mixed solvothermal synthesis technology, nanobelt-based Sb2Se3 whiskers were fabricated in the mixed solvent of C2H5OH and N2H4·H2O with the volume ratio of 2:1 at 160-180 ºC for 12 h, using SbCl3 and SeO2 as starting reactant. The products are characterized by X-ray diffraction, field-emission scanning electron microscopy and transmission electron microscopy. The volume ratio of ethanol and hydrazine hydrate influences the morphology of Sb2Se3 products. The diameters of Sb2Se3 whiskers range from 0.4 to 1.2 μm and length is up to 30 μm. The whisker is assembled by multi-layered Sb2Se3 nanobelts and the growth mechanism is simply studied.